1981
DOI: 10.1161/01.res.49.6.1262
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary adenosine deaminase reduces canine myocardial reactive hyperemia.

Abstract: SUMMARY We employed intracoronary infusions of calf intenstine adenosine deaminase (ADA) to test the hypothesis that adenosine regulates coronary blood flow during myocardial reactive hyperemia (RH). Infusions of 4.5 U ADA/min per kg body weight into the left circumflex coronary artery of 10 open-chest dogs reversibly reduced repayment of flow debt by 30-39% ( P < 0.05) following 5-, 10-, 15-, 20-, and 30-second coronary occlusions, the percentage reduction being independent of occlusion length. ADA reduced pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
43
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 23 publications
13
43
0
Order By: Relevance
“…Importantly, however, other studies provide compelling data to indicate that adenosine plays no role in coronary reactive hyperemia (8). Our data are more like those of Bittar and Pauly (8) than those of Saito et al (46). The development of arginine analogs soon placed NO on the list of mediators of reactive hyperemia.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Importantly, however, other studies provide compelling data to indicate that adenosine plays no role in coronary reactive hyperemia (8). Our data are more like those of Bittar and Pauly (8) than those of Saito et al (46). The development of arginine analogs soon placed NO on the list of mediators of reactive hyperemia.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, exogenous adenosine (at levels comparable to ischemic production) elicits vasodilation equal to that observed in reactive hyperemia (38). Finally, adenosine deaminase reversibly reduces hyperemic flow (without any effect on peak) following an occlusion longer than 5 s (46). These data solidify the place of adenosine on the list of viable mediators of reactive hyperemia.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have demonstrated that endogenous adenosine is not obligatory for maintaining coronary blood flow during normal arterial inflow. Thus, studies in anesthetized open-chest dogs (15)(16)(17)(18)(19) and awake dogs (1,20) failed to demonstrate an effect of intracoronary adenosine deaminase (15)(16)(17), or adenosine receptor blockade with intravenous aminophylline (18, 19) or 8-phenyltheophylline (1, 20), on (21) examined the effect of exercise on myocardial adenosine production. They found that treadmill exercise in dogs resulted in a fivefold increase in myocardial adenosine content, with a doubling of the coronary arterio-venous adenosine content difference.…”
Section: Discussionmentioning
confidence: 99%
“…43 Adenosine deaminase reduced coronary reactive hyperemia after a brief period of ischemia by 27-36%. 44 These observations support a substantial role of adenosine in mediating ischemia-induced coronary hyperemic flow. The constituents of reactive hyperemia other than adenosine remain to be determined.…”
Section: Roles Of Adenosine In Coronary Hyperemicmentioning
confidence: 64%